Proposed upgrading Ilham Bestari Academy at No. 31,33,35,37, Persiaran Seri Raia, Taman Seri Raia, 37300 Ipoh, Perak Darul Ridzuan for Tulus Motivasi Sdn. Bhd. / Faezah Shafiee - Shafiee, Faezah (Faculty of Architecture, Planning and Surveying, 2012)
All final student of Diploma in Interior Architecture should be able to complete every stage of their final design. This purposed is to analysis student knowlegde about interior design from basic to full presentation in board. Proposed upgarading of Ilham Bestari Academy at Persiaran Seri Raia, Taman Seri Raia, Simpang Pulai, Perak Darul Ridzuan has been chosen for this final project. The choose of this project because the client want to change the current space design and enviroment in the academy. This because the client want the academy to get new enviroment for the student so that the student will more comfortable to study. Furthermore, it can also introduce this academy to the market so it become well known to people and can attract student to enroll in this company. Concept and images for this academy is reflect to the client’s needed. There are few method in gathering some information. The method that can be used in gathering information for this project is throughout interview, observation, internet and case study. The choosen project is about upgrading Ilham Bestari Academy that focus on upgrading the certain space in this academy. This academy have been provided two main course such sewing course for female student and also automotive course for male student and other sub short course. The space that focus to upgrade in this academy at office area and sewing classes area. The client of this project which is the Ilham Bestari Academy want to change the current enviroment to the new design to make the all area are well arrange and become more interesting.